A Novel Tetrahydrofuranyl Fatty Acid from a New Microbial Isolate, Pestalotia sp. YIM 69032 Cultivated in Extract of Potato. (18th September 2012) - Yang, Xueqiong; Yang, Yabin; Zhao, Lixing; Zhou, Hao; Xu, Lihua; Ding, Zhongtao
Abstract: A novel tetrahydrofuranyl fatty acid (THFA) and a rare natural ( R )‐configuration phenylethanediol were isolated from potato extract media in which Pestalotia sp. YIM 69032 had been cultivated. On the basis of spectral data including of HRMS, NMR and 2D NMR, their structures were determined as (3 R, 5 S, 6 R, 7 S, 8 Z )‐8‐en‐5, 7‐dihydroxy‐3, 6‐epoxy‐tetradecanoic acid (1 ) and ( R )‐1‐(3‐ethylphenyl)‐1, 2‐ethanediol (2 ). Thus, a new microbial isolate, Pestalotia sp. was found to produce THFA. The possible pathway from tetradecanoic acid (4 ) to THFA (1 ) in the extract of potato by Pestalotia sp. was proposed. Structures1 and2 showed no cytotoxicity against HL‐60, SMMC‐7721, A‐549, MCF‐7, SW480 cell lines.